Production method of niobium-containing microalloyed high-strength steel

By regulating the content and structure of niobium, gallium, thallium, tellurium, antimony, carbon, manganese, silicon and carbon nanofibers in high-strength steel, forming fine crystal and oriented growth structures, it is difficult to take into account the strength and toughness of existing steels. The problem of insufficient corrosion resistance has achieved efficient production process and excellent comprehensive performance.

CN119194253APending Publication Date: 2024-12-27WUHAN YIZHINIAO TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411313326.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing high-strength steels often sacrifice toughness while increasing their strength, lack corrosion resistance, low utilization efficiency of alloy elements, and poor processing performance, making it difficult to meet the high-end application needs in the fields of construction, bridges, automobiles, etc.

Method used

The production method of microalloyed high-strength steel containing niobium is adopted to accurately regulate the content and microstructure of iron, niobium, gallium, thallium, tellurium, antimony, carbon, manganese, silicon and carbon nanofibers to form fine crystal reinforcement and dispersion reinforcement. and guide growth structure to optimize the mechanical properties and oxidation resistance of steel.

Benefits of technology

It significantly improves the strength, toughness, oxidation resistance and corrosion resistance of steel, realizes an efficient and stable production process, and is widely used in multiple fields, providing high-performance and high-quality material support for related industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194253A_ABST
    Figure CN119194253A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of niobium-containing steel, in particular to a production method of niobium-containing microalloyed high-strength steel, which overcomes the defects in the prior art and comprises the following components: 90 to 95 parts of iron, 0.05 to 0.2 part of niobium, 0.01 to 0.05 part of gallium, 0.001 to 0.01 part of thallium, 0.01 to 0.05 part of tellurium, 0.01 to 0.1 part of antimony, 0.3 to 0.8 part of carbon, 1 to 3 parts of manganese, 0.5 to 2 parts of silicon and 0.05 to 0.2 part of carbon nanofiber. Through an elaborately designed component formula, such as niobium, gallium, thallium, manganese, silicon and carbon nanofibers, the fine grain strengthening and dispersion strengthening effects are promoted through the unique alloy element proportion, the microstructure of the steel is further strengthened through the ingenious fusion of the carbon nanofibers, and through the synergistic effect of niobium precipitates and the carbon nanofibers, the mechanical property of the steel is improved. A unique strengthened phase network and twin crystal structure is formed, and the overall performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-strength steel, and in particular to a method for producing niobium-containing microalloyed high-strength steel. Background Art

[0002] With the continuous advancement of industrial technology, the requirements for steel performance are also increasing. Especially in the fields of construction, bridges, automobiles, ships, petrochemicals, etc., the demand for high-strength, high-toughness, corrosion-resistant and excellent weldability steel is growing. Traditional steel can no longer meet the needs of these high-end applications. Therefore, the development of new high-performance steel has become an important research topic in the current metallurgical field. As a new type of high-performance steel, niobium-containing microalloyed high-strength steel has gradually become a research hotspot with its excellent mechanical properties and processing properties.

[0003] In the prior art, although the performance of steel can be improved to a certain extent by alloying, heat treatment and other means, there are still the following shortcomings:

[0004] 1. It is difficult to strike a balance between strength and toughness: Traditional steels often sacrifice toughness while increasing their strength, causing the steel to easily fracture brittlely under complex stress environments.

[0005] 2. Limited corrosion resistance: In corrosive environments such as marine engineering and petrochemical industry, traditional steel has insufficient corrosion resistance and limited service life.

[0006] 3. Low efficiency of alloying elements: Some alloying elements are unevenly distributed in steel, resulting in poor alloying effect and increasing production costs.

[0007] 4. Poor processing performance: Although some high-strength steels have excellent mechanical properties, their processing performance such as welding and forming is poor, which limits their application range.

[0008] Therefore, we proposed a method for producing niobium-containing microalloyed high-strength steel to solve the above problems. Summary of the invention

[0009] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a method for producing niobium-containing microalloyed high-strength steel.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] A niobium-containing microalloyed high-strength steel comprises the following components in parts by weight: 90-95 parts of iron, 0.05-0.2 parts of niobium, 0.01-0.05 parts of gallium, 0.001-0.01 parts of thallium, 0.01-0.05 parts of tellurium, 0.01-0.1 parts of antimony, 0.3-0.8 parts of carbon, 1-3 parts of manganese, 0.5-2 parts of silicon and 0.05-0.2 parts of carbon nanofiber.

[0012] As the preferred technical solution:

[0013] The niobium-containing microalloyed high-strength steel as described above comprises the following components in parts by weight: 93 parts of iron, 0.1 parts of niobium, 0.03 parts of gallium, 0.005 parts of thallium, 0.03 parts of tellurium, 0.05 parts of antimony, 0.5 parts of carbon, 2 parts of manganese, 1 part of silicon, and 0.1 parts of carbon nanofibers.

[0014] In the niobium-containing microalloyed high-strength steel as described above, the average grain size of the iron is 10-15 μm, the ellipticity of the niobium is 1.2-1.5, the average particle size of the carbide particles formed by the carbon and niobium is 50-70 nm, and the fiber diameter of the carbon nanofiber is 10-50 nm.

[0015] In the niobium-containing microalloyed high-strength steel as described above, the manganese exists in the steel in the form of precipitates, and the average particle size of the precipitates is 50-100 nm, so as to improve the strength and hardenability of the steel; the silicon exists in the steel in the form of a solid solution, and part of the silicon forms compounds with other elements in the steel, and the particle size of these compounds is 50-80 nm, so as to optimize the oxidation resistance and corrosion resistance of the steel.

[0016] A niobium-containing microalloyed high-strength steel as described above, wherein in the microstructure of the steel, niobium carbide particles are uniformly distributed at grain boundaries and within grains, and at least 50% of the niobium carbide particles are adjacent to carbon nanofibers to form a strengthening phase network;

[0017] The carbon nanofibers form a specific arrangement or network structure in the material, such as a three-dimensional interwoven network. The carbon nanofibers act as a guiding structure to guide the crystals to grow in a specific direction. In the niobium-containing microalloyed high-strength steel, the niobium element exists in the form of fine precipitates. These precipitates interact with the carbon nanofibers. The precipitates gather around the carbon nanofibers to form a precipitate shell. The possibility of twin formation is set as P, then

[0018]

[0019] Where A is a constant related to material properties; ΔE is the energy required for twin formation; U eff is a measure of the effective interaction energy between the precipitate and the carbon nanofiber; k is the Boltzmann constant; T is the absolute temperature; Reff is the effective crystal growth rate; C eff is the effective precipitate concentration at the key position for twin formation.

[0020] A second aspect of the present invention provides a method for producing a niobium-containing microalloyed high-strength steel, comprising the following steps:

[0021] S1: Add iron into the induction furnace for preliminary smelting, and adjust the smelting temperature and atmosphere to remove impurities and adjust the initial composition of the molten iron;

[0022] S2: When the temperature of the molten iron decreases, niobium oxide is slowly added, and mechanical stirring is used to ensure that niobium is evenly distributed in the molten iron. Advanced sensors and control systems are used to monitor the distribution of niobium in real time and adjust the feeding and stirring parameters in time;

[0023] S3: After the niobium element is added and evenly distributed, add manganese with a higher melting point first, and then add silicon after it is fully dissolved. Control the addition speed and stirring intensity to ensure that these elements are evenly distributed in the molten iron;

[0024] S4: Finally, trace elements such as gallium, thallium, tellurium, and antimony are added, and the ultrasonic generator is turned on to use the cavitation effect and mechanical vibration of the ultrasonic wave to promote the uniform dispersion of the trace elements in the molten iron;

[0025] S5: According to the carbon content requirement of the final product, carbon is gradually added, and at the same time, the carbon content in the molten steel is adjusted by blowing oxygen;

[0026] S6: before the end of smelting, when the temperature of the molten steel drops to a certain range, slowly add the carbon nanofibers, and evenly disperse the carbon nanofibers in the molten steel through an ultrasonic vibration disperser, and start a high-speed rotating stirrer while adding the carbon nanofibers to further promote the even dispersion of the carbon nanofibers in the molten steel;

[0027] S7: After adding all the elements, the temperature of the molten steel is kept stable for a period of time to ensure that all the elements and the carbon nanofibers fully react and combine;

[0028] S8: The treated molten steel is poured into a mold, and a billet is obtained after cooling and solidification. During the casting process, the casting speed and cooling rate need to be controlled to avoid defects in the billet.

[0029] As the preferred technical solution:

[0030] In the above-mentioned method for producing niobium-containing microalloyed high-strength steel, in S3, after the niobium element is added and evenly distributed, the temperature of the molten iron is maintained at 1400-1450°C, manganese with a higher melting point is added first, and after manganese is fully dissolved, when the temperature of the molten iron drops to 1350-1400°C, silicon is added, and the addition rate of manganese and silicon is controlled at 4-6kg / min, and the stirring intensity is 200-300rpm to ensure the uniform distribution of these elements in the molten iron.

[0031] A method for producing niobium-containing microalloyed high-strength steel as described above, in S6, before the end of smelting, when the temperature of the molten steel drops to 1200-1300°C, carbon nanofibers are slowly added, and the length of the carbon nanofibers is controlled between 10 and 50 μm. The carbon nanofibers are uniformly dispersed in the molten steel by an ultrasonic vibration disperser, and the power of the ultrasonic vibration disperser is set to 2-3 kW. While adding the carbon nanofibers, a high-speed rotating agitator is turned on and the stirring speed is set to 200-400 rpm, so as to further promote the uniform dispersion of the carbon nanofibers in the molten steel.

[0032] In the method for producing niobium-containing microalloyed high-strength steel as described above, the carbon nanofibers are subjected to surface modification treatment by exposing them to an oxidizing gas so as to introduce oxygen-containing functional groups onto the surface of the carbon nanofibers. At the same time, a thin organic coating is coated on the surface of the carbon nanofibers to change their surface properties.

[0033] Compared with the prior art, the present invention achieves a significant improvement in mechanical properties, oxidation resistance and corrosion resistance by precisely controlling the content and microstructure of components such as iron, niobium, gallium, thallium, tellurium, antimony, carbon, manganese, silicon and carbon nanofibers. The addition of niobium enhances the strength and toughness of steel through fine grain strengthening and dispersion strengthening mechanisms, while carbon nanofibers act as guiding structures to guide the directional growth of crystals and synergize with niobium carbide particles to form a unique strengthening phase network and twin structure, further improving the comprehensive performance of steel. In addition, the presence of silicon in the form of solid solution and compounds optimizes the oxidation resistance of steel, while the reasonable addition of elements such as manganese improves the hardenability of steel. Therefore, the niobium-containing microalloyed high-strength steel not only has excellent mechanical properties, oxidation resistance and corrosion resistance, but also has an efficient and stable production process, and is widely used in many fields such as automobiles, aerospace, construction, bridges, etc., providing high-performance and high-quality material support for the progress and development of related industries.

[0034] Beneficial effects:

[0035] As a microalloying element, niobium can form fine precipitates in steel, which can refine grains through the pinning effect and achieve fine-grain strengthening. At the same time, these precipitates can also be dispersed in the matrix, hindering dislocation movement and playing a role of dispersion strengthening. The synergistic effect of these two strengthening mechanisms significantly improves the strength of steel. The addition of carbon nanofibers provides additional strengthening phases for steel. Not only do they have high strength and high modulus themselves, they can also act as templates to guide precipitates such as niobium carbides to gather around them to form a strengthening phase network. This composite strengthening structure enables the steel to disperse stress more effectively when under load and improve the overall mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 It is a line graph of tensile performance data of the embodiments and comparative examples of the present invention;

[0037] Figure 2 It is a bar chart of hardness data of the embodiments and comparative examples of the present invention. DETAILED DESCRIPTION

[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. In the event of a conflict, the definitions in the specification shall prevail. "When mass, concentration, temperature, time, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 should be understood to include 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91 6, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, any number, combination of numbers, or subrange, and all decimal values ​​between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested subranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction."

[0039] The present invention is further explained below in conjunction with specific examples. The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are all commercially available unless otherwise specified.

[0040] A niobium-containing microalloyed high-strength steel comprises the following components in parts by weight: 90-95 parts of iron, 0.05-0.2 parts of niobium, 0.01-0.05 parts of gallium, 0.001-0.01 parts of thallium, 0.01-0.05 parts of tellurium, 0.01-0.1 parts of antimony, 0.3-0.8 parts of carbon, 1-3 parts of manganese, 0.5-2 parts of silicon and 0.05-0.2 parts of carbon nanofiber.

[0041] The average grain size of the iron is 10-15 μm, the ellipticity of the niobium is 1.2-1.5, the average particle size of the carbide particles formed by the carbon and niobium is 50-70 nm, and the fiber diameter of the carbon nanofiber is 10-50 nm.

[0042] The manganese exists in the steel in the form of precipitates, and the average particle size of the precipitates is 50-100 nm, so as to improve the strength and hardenability of the steel. The silicon exists in the steel in the form of a solid solution, and part of the silicon forms compounds with other elements in the steel. The particle size of these compounds is 50-80 nm, so as to optimize the oxidation resistance and corrosion resistance of the steel.

[0043] In the microstructure of the steel, niobium carbide particles are uniformly distributed at grain boundaries and within grains, and at least 50% of the niobium carbide particles are adjacent to carbon nanofibers to form a strengthening phase network;

[0044] The carbon nanofibers form a three-dimensional interwoven network in the material. The carbon nanofibers serve as a guiding structure to guide the crystals to grow in the horizontal direction. In the niobium-containing microalloyed high-strength steel, the niobium element exists in the form of fine precipitates. These precipitates interact with the carbon nanofibers. The precipitates gather around the carbon nanofibers to form a precipitate shell. The possibility of twin formation is set as P, then:

[0045]

[0046] Where A is a constant related to material properties; ΔE is the energy required for twin formation; U eff is a measure of the effective interaction energy between the precipitate and the carbon nanofiber; k is the Boltzmann constant; T is the absolute temperature; R eff is the effective crystal growth rate; C eff is the effective precipitate concentration at the key position for twin formation.

[0047] Arrangement and network structure of carbon nanofibers:

[0048] The carbon nanofibers form a three-dimensional interwoven network in the material. This network structure not only enhances the strength and toughness of the steel, but also acts as a guide structure to guide the crystals to grow in the horizontal direction.

[0049] Niobium element precipitate:

[0050] Niobium exists in the steel in the form of fine precipitates, which refine the grains through the pinning effect and increase the strength of the steel through the dispersion strengthening mechanism.

[0051] Interaction between precipitates and carbon nanofibers:

[0052] There is a strong interaction between the precipitates and the carbon nanofibers. This interaction causes the precipitates to aggregate around the carbon nanofibers to form a precipitate shell. This shell structure further strengthens the microstructure of the steel.

[0053] Twin formation:

[0054] Twins are a special type of crystal defect that has an important impact on the properties of steel. The probability of twin formation (P) is related to several factors, including a constant related to the material properties (A), the energy or stress threshold required for twin formation (ΔE), a measure of the effective interaction energy between the precipitates and the carbon nanofibers (U eff ), Boltzmann constant (k), absolute temperature (T), effective crystal growth rate (R eff ) and the effective precipitate concentration (C eff ).

[0055] Material properties:

[0056] The carbon content of the steel is 0.5% (moderate), and the alloying element ratio is 92 parts of iron, 0.1 parts of niobium, 0.03 parts of gallium, 0.005 parts of thallium, 0.03 parts of tellurium, 0.05 parts of antimony, 2 parts of manganese, 1 part of silicon, and 0.1 parts of carbon nanofiber.

[0057] The constant A related to material properties is set to 1.

[0058] Interaction between precipitates and carbon nanofibers:

[0059] The precipitates are niobium carbides with an average size of 50 nanometers, which are evenly distributed around the carbon nanofibers to form a precipitate shell.

[0060] The effective interaction energy U between the precipitate and the carbon nanofibers eff Set to -0.5 eV (negative values ​​indicate attraction).

[0061] Temperature and crystal growth rate:

[0062] The absolute temperature T is 800 degrees Celsius (about 1073 Kelvin).

[0063] Effective crystal growth rate R eff It is 10^-6m / s.

[0064] Precipitate concentration:

[0065] The effective precipitate concentration C at the key position of twin formation eff It is 1018 pieces / m3.

[0066] Energy or stress threshold required for twin formation:

[0067] The energy ΔE required for twin formation was set to 0.1 eV.

[0068] Detailed description of the twin formation process

[0069] Under the above assumptions, when steel undergoes heat treatment processes (such as quenching and tempering), the following processes occur:

[0070] Interaction between precipitates and carbon nanofibers: Due to the strong attraction between precipitates and carbon nanofibers (U eff =-0.5 eV), the precipitates tend to aggregate around the carbon nanofibers to form a stable precipitate shell.

[0071] Crystal growth and twin formation: At appropriate temperature and crystal growth rate (T = 800 degrees Celsius, R eff =10^-6m / s), the crystal grows along the guiding direction of the carbon nanofiber. Due to the existence of the precipitate shell, the crystal is easily hindered during growth, resulting in stress concentration in the local area. When the stress reaches the threshold required for twin formation (ΔE=0.1eV), the twin structure begins to form.

[0072] Effect of precipitate concentration: At the key position of twin formation, the concentration of precipitates reaches an appropriate level (C eff = 1018 pieces / m3). This is neither too high (resulting in too many precipitates hindering crystal growth) nor too low (failure to form an effective precipitate shell).

[0073] Embodiment 1

[0074] A niobium-containing microalloyed high-strength steel comprises the following components in parts by weight: 90 parts of iron, 0.05 parts of niobium (CITIC Metal Co., Ltd.), 0.01 parts of gallium (Orient Tantalum Co., Ltd.), 0.001 parts of thallium (Sinopharm Chemical Reagent Co., Ltd.), 0.01 parts of tellurium (China Tungsten Online Technology Co., Ltd.), 0.01 parts of antimony (Hunan Gold Group Co., Ltd.), 0.3 parts of carbon, 1 part of manganese (Hesteel Group Co., Ltd.), 0.5 parts of silicon, and 0.05 parts of carbon nanofiber (Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences).

[0075] The present invention provides a method for producing a niobium-containing microalloyed high-strength steel, comprising the following steps:

[0076] S1: Add iron into the induction furnace, use the induction furnace with a power of 500kW for preliminary smelting, initially set to 1500℃, use argon protection, control the flow rate at 5L / min, avoid oxidation of the molten iron, and adjust the initial composition of the molten iron;

[0077] S2: When the temperature of the molten iron drops to 1400℃, niobium oxide is slowly added in a step-by-step manner. The mechanical stirring speed is set to 200rpm to ensure the uniform distribution of niobium in the molten iron. High-precision temperature sensors and niobium element distribution sensors are used to monitor the distribution of niobium in real time and adjust the feeding and stirring parameters in time.

[0078] S3: After the niobium element is added and evenly distributed, the temperature of the molten iron is maintained at 1400°C, and manganese with a higher melting point is added first. After manganese is fully dissolved and the temperature of the molten iron drops to 1350°C, silicon is added. The addition rate of manganese and silicon is controlled at 4kg / min, and the stirring intensity is 200rpm to ensure the even distribution of these elements in the molten iron;

[0079] S4: Keep the temperature of the molten iron at 1300°C, and finally add trace elements of gallium, thallium, tellurium and antimony in small batches and multiple additions, with the amount added each time not exceeding 5% of the total amount added. Turn on the ultrasonic generator and use the cavitation effect and mechanical vibration of the ultrasonic wave to promote the uniform dispersion of the trace elements in the molten iron;

[0080] S5: according to the carbon content requirement of the final product, gradually add carbon, the amount added each time shall not exceed 10% of the total amount added, and at the same time, adjust the carbon content in the molten steel by blowing oxygen, and control it within 10 minutes;

[0081] S6: before the end of smelting, when the temperature of the molten steel drops to 1200°C, slowly add carbon nanofibers, the length of the carbon nanofibers is controlled to be 10 μm, and the carbon nanofibers are evenly dispersed in the molten steel by an ultrasonic vibration disperser, the power of the ultrasonic vibration disperser is set to 2 kW, and while adding the carbon nanofibers, the high-speed rotating stirrer is turned on and the stirring speed is set to 200 rpm, so as to further promote the uniform dispersion of the carbon nanofibers in the molten steel;

[0082] S7: After adding all the elements, the temperature of the molten steel is kept stable at about 1200°C for 15 minutes to ensure that all the elements and the carbon nanofibers fully react and combine;

[0083] S8: Pour the treated molten steel into a mold at 1150°C and a casting speed of 5kg / s. After cooling and solidification, a cast billet is obtained. During the casting process, the casting speed and cooling rate need to be controlled to avoid defects in the cast billet.

[0084] Embodiment 2

[0085] A niobium-containing microalloyed high-strength steel comprises the following components in parts by weight: 95 parts of iron, 0.2 parts of niobium, 0.05 parts of gallium, 0.01 parts of thallium, 0.05 parts of tellurium, 0.1 parts of antimony, 0.8 parts of carbon, 3 parts of manganese, 2 parts of silicon and 0.2 parts of carbon nanofiber.

[0086] The present invention provides a method for producing a niobium-containing microalloyed high-strength steel, comprising the following steps:

[0087] S1: Add iron into the induction furnace, use the induction furnace with a power of 500kW for preliminary smelting, initially set to 1600℃, use argon protection, control the flow rate at 7L / min, avoid oxidation of the molten iron, and adjust the initial composition of the molten iron;

[0088] S2: When the temperature of the molten iron drops to 1450°C, niobium oxide is slowly added in a step-by-step manner. The mechanical stirring speed is set to 300 rpm to ensure uniform distribution of niobium in the molten iron. High-precision temperature sensors and niobium element distribution sensors are used to monitor the distribution of niobium in real time and adjust the feeding and stirring parameters in time.

[0089] S3: After the niobium element is added and evenly distributed, the temperature of the molten iron is maintained at 1450°C, and manganese with a higher melting point is added first. After manganese is fully dissolved and the temperature of the molten iron drops to 1400°C, silicon is added. The addition rate of manganese and silicon is controlled at 6kg / min, and the stirring intensity is 300rpm to ensure the even distribution of these elements in the molten iron;

[0090] S4: Keep the temperature of the molten iron at 1350°C, and finally add trace elements of gallium, thallium, tellurium and antimony in small batches and multiple additions, with the amount added each time not exceeding 5% of the total amount added. Turn on the ultrasonic generator and use the cavitation effect and mechanical vibration of the ultrasonic wave to promote the uniform dispersion of the trace elements in the molten iron;

[0091] S5: according to the carbon content requirement of the final product, carbon is gradually added, and the amount added each time does not exceed 10% of the total amount added. At the same time, the carbon content in the molten steel is adjusted by blowing oxygen, and the process is controlled within 30 minutes;

[0092] S6: before the end of smelting, when the temperature of the molten steel drops to 1300°C, slowly add carbon nanofibers, the length of the carbon nanofibers is controlled to be 50 μm, and the carbon nanofibers are evenly dispersed in the molten steel by an ultrasonic vibration disperser, the power of the ultrasonic vibration disperser is set to 3 kW, and while adding the carbon nanofibers, the high-speed rotating stirrer is turned on and the stirring speed is set to 400 rpm, so as to further promote the uniform dispersion of the carbon nanofibers in the molten steel;

[0093] S7: After adding all the elements, the temperature of the molten steel is kept stable at 1300°C for 20 minutes to ensure that all the elements and the carbon nanofibers fully react and combine;

[0094] S8: Pour the treated molten steel into a mold at 1200°C and a casting speed of 10kg / s. After cooling and solidification, a cast billet is obtained. During the casting process, the casting speed and cooling rate need to be controlled to avoid defects in the cast billet.

[0095] Embodiment 3

[0096] A niobium-containing microalloyed high-strength steel comprises the following components in parts by weight: 92 parts of iron, 0.08 parts of niobium, 0.02 parts of gallium, 0.005 parts of thallium, 0.02 parts of tellurium, 0.02 parts of antimony, 0.4 parts of carbon, 1.2 parts of manganese, 0.8 parts of silicon and 0.09 parts of carbon nanofiber.

[0097] The present invention provides a method for producing a niobium-containing microalloyed high-strength steel, comprising the following steps:

[0098] S1: Add iron into the induction furnace, use the induction furnace with a power of 500kW for preliminary smelting, initially set at 1525℃, use argon protection, control the flow rate at 5.5L / min, avoid oxidation of the molten iron, and adjust the initial composition of the molten iron;

[0099] S2: When the temperature of the molten iron drops to 1410°C, niobium oxide is slowly added in a step-by-step manner. The mechanical stirring speed is set to 220rpm to ensure uniform distribution of niobium in the molten iron. High-precision temperature sensors and niobium element distribution sensors are used to monitor the distribution of niobium in real time and adjust the feeding and stirring parameters in time.

[0100] S3: After the niobium element is added and evenly distributed, the temperature of the molten iron is maintained at 1410°C, and manganese with a higher melting point is added first. After manganese is fully dissolved and the temperature of the molten iron drops to 1360°C, silicon is added. The addition rate of manganese and silicon is controlled at 4.5kg / min, and the stirring intensity is 220rpm to ensure the even distribution of these elements in the molten iron;

[0101] S4: Keep the temperature of the molten iron at 1310°C, and finally add trace elements of gallium, thallium, tellurium and antimony in small batches and multiple additions, with the amount added each time not exceeding 5% of the total amount added. Turn on the ultrasonic generator and use the cavitation effect and mechanical vibration of the ultrasonic wave to promote the uniform dispersion of the trace elements in the molten iron;

[0102] S5: according to the carbon content requirement of the final product, carbon is gradually added, and the amount added each time does not exceed 10% of the total amount added. At the same time, the carbon content in the molten steel is adjusted by blowing oxygen, and the process is controlled within 15 minutes;

[0103] S6: before the end of smelting, when the temperature of the molten steel drops to 1220°C, slowly add carbon nanofibers, the length of the carbon nanofibers is controlled to be 20 μm, and the carbon nanofibers are evenly dispersed in the molten steel by an ultrasonic vibration disperser, the power of the ultrasonic vibration disperser is set to 2.2 kW, and while adding the carbon nanofibers, the high-speed rotating stirrer is turned on and the stirring speed is set to 250 rpm, so as to further promote the uniform dispersion of the carbon nanofibers in the molten steel;

[0104] S7: After adding all the elements, the temperature of the molten steel is kept stable at 1220°C for 16 minutes to ensure that all the elements and the carbon nanofibers fully react and combine;

[0105] S8: Pour the treated molten steel into a mold, control the temperature at 1170°C, and the casting speed at 6kg / s, and obtain a cast billet after cooling and solidification. The casting speed and cooling rate need to be controlled during the casting process to avoid defects in the cast billet.

[0106] Embodiment 4

[0107] A niobium-containing microalloyed high-strength steel comprises the following components in parts by weight: 94 parts of iron, 0.18 parts of niobium, 0.04 parts of gallium, 0.009 parts of thallium, 0.04 parts of tellurium, 0.09 parts of antimony, 0.7 parts of carbon, 2.6 parts of manganese, 1.5 parts of silicon and 0.15 parts of carbon nanofiber.

[0108] The present invention provides a method for producing a niobium-containing microalloyed high-strength steel, comprising the following steps:

[0109] S1: Add iron into the induction furnace, use the induction furnace with a power of 500kW for preliminary smelting, initially set at 1580℃, use argon protection, control the flow rate at 6.5L / min, avoid oxidation of the molten iron, and adjust the initial composition of the molten iron;

[0110] S2: When the temperature of the molten iron drops to 1440°C, niobium oxide is slowly added in a step-by-step manner. The mechanical stirring speed is set to 280rpm to ensure uniform distribution of niobium in the molten iron. High-precision temperature sensors and niobium element distribution sensors are used to monitor the distribution of niobium in real time and adjust the feeding and stirring parameters in time.

[0111] S3: After the niobium element is added and evenly distributed, the temperature of the molten iron is maintained at 1440°C, and manganese with a higher melting point is added first. After manganese is fully dissolved and the temperature of the molten iron drops to 1380°C, silicon is added. The addition rate of manganese and silicon is controlled at 5.5kg / min, and the stirring intensity is 280rpm to ensure the even distribution of these elements in the molten iron;

[0112] S4: Keep the temperature of the molten iron at 1340°C, and finally add trace elements of gallium, thallium, tellurium and antimony in small batches and multiple additions, with the amount added each time not exceeding 5% of the total amount added. Turn on the ultrasonic generator and use the cavitation effect and mechanical vibration of the ultrasonic wave to promote the uniform dispersion of the trace elements in the molten iron;

[0113] S5: according to the carbon content requirement of the final product, carbon is gradually added, and the amount added each time does not exceed 10% of the total amount added. At the same time, the carbon content in the molten steel is adjusted by blowing oxygen, and the process is controlled within 28 minutes;

[0114] S6: before the end of smelting, when the temperature of the molten steel drops to 1280°C, slowly add carbon nanofibers, the length of the carbon nanofibers is controlled to be 40 μm, and the carbon nanofibers are evenly dispersed in the molten steel by an ultrasonic vibration disperser, the power of the ultrasonic vibration disperser is set to 2.8 kW, and while adding the carbon nanofibers, the high-speed rotating stirrer is turned on and the stirring speed is set to 280 rpm, so as to further promote the uniform dispersion of the carbon nanofibers in the molten steel;

[0115] S7: After adding all the elements, the temperature of the molten steel is kept stable at 1280°C for 18 minutes to ensure that all the elements and the carbon nanofibers fully react and combine;

[0116] S8: Pour the treated molten steel into a mold, control the temperature at 1180°C, and the casting speed at 9kg / s, and obtain a cast billet after cooling and solidification. The casting speed and cooling rate need to be controlled during the casting process to avoid defects in the cast billet.

[0117] Embodiment 5

[0118] On the basis of Example 4, the carbon nanofibers are surface modified by exposing them to an oxidizing gas to introduce oxygen-containing functional groups onto the surface of the carbon nanofibers. At the same time, a thin organic coating is applied onto the surface of the carbon nanofibers to change their surface properties.

[0119] The specific steps are as follows:

[0120] S1: Iron was added to a 500kW induction furnace, set at 1580°C for preliminary smelting, argon protection (6.5L / min) was used to prevent oxidation, and the initial composition was adjusted.

[0121] S2: When the molten iron temperature drops to 1440℃, slowly add niobium oxide and mechanically stir at 280rpm. Use sensors to monitor and adjust to ensure uniform distribution of niobium.

[0122] S3: After adding niobium, add manganese while maintaining 1440℃. After manganese is dissolved, reduce the temperature to 1380℃ and add silicon. Control the adding speed to 5.5kg / min and stir at 280rpm to ensure uniformity.

[0123] S4: The temperature is lowered to 1340°C, trace elements (gallium, thallium, tellurium, antimony) are added in small batches and multiple times, and ultrasound is turned on to promote uniform dispersion.

[0124] S5: Add carbon gradually according to the carbon content requirement and adjust by blowing oxygen for 28 minutes.

[0125] S6 (improvement step): Surface modification of carbon nanofibers, introduction of oxygen-containing functional groups and coating with organic coating (polyvinyl acetate). When the molten steel drops to 1280°C, pretreated carbon nanofibers (40 μm) are added, and ultrasonic waves (2.8 kW) are combined with high-speed stirring (280 rpm) to ensure uniform dispersion.

[0126] S7: Maintain the temperature at 1280°C for 18 minutes to ensure that all elements react and combine.

[0127] S8: Casting into the mold, the temperature is controlled at 1180℃, the speed is 9kg / s, and attention is paid to controlling the casting and cooling rates to avoid defects.

[0128] Through the above steps, the surface modification treatment can improve the dispersion of carbon nanofibers in molten steel or other matrix materials, reduce agglomeration, and ensure the uniform distribution of carbon nanofibers in the matrix. The surface modification treatment also helps to improve the heat resistance, durability and other properties of the composite material, so that it can maintain stable performance even in harsh environments.

[0129] Comparative Example 1

[0130] A method for producing niobium-containing microalloyed high-strength steel is basically the same as that of the fourth embodiment, except that the use of niobium in the high-strength steel is eliminated.

[0131] Comparative Example 2

[0132] A method for producing niobium-containing microalloyed high-strength steel is basically the same as the fourth embodiment, except that the application of carbon nanofibers in the high-strength steel is removed.

[0133] Comparative Example 3

[0134] A method for producing niobium-containing microalloyed high-strength steel is basically the same as the fourth embodiment, except that the use of manganese in the high-strength steel is removed.

[0135] Comparative Example 4

[0136] A method for producing niobium-containing microalloyed high-strength steel is basically the same as that of the fourth embodiment, except that the application of niobium and carbon nanofibers in the high-strength steel is removed.

[0137] The niobium-containing microalloyed high-strength steels prepared in the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 4 were tested, and the testing standards were as follows:

[0138] GB / T 228.1-2021: This standard specifies the method for tensile testing of metallic materials at room temperature, which is one of the main standards for evaluating the tensile properties (strength, plasticity, etc.) of steel.

[0139] GB / T 231.1-2018: This standard specifies the method for Brinell hardness test of metal materials. Brinell hardness is also one of the important indicators in hardness test.

[0140] GB / T 229-2020: This standard specifies the Charpy pendulum impact test method for determining the energy absorbed by impact specimens of metal materials in impact tests. It is applicable to impact tests under room temperature, high temperature or low temperature conditions.

[0141] GB / T 25834-2010: This standard specifies the method for outdoor atmospheric accelerated corrosion testing of steel, which evaluates the corrosion resistance of steel by simulating the natural exposure to atmospheric corrosion environment.

[0142] The niobium-containing microalloyed high-strength steels prepared in the above-mentioned Examples 1 to 5 and Comparative Examples 1 to 4 were tested, and the results are shown in Table 1 below:

[0143] Table 1

[0144] Tensile properties (MPa) Hardness (HB) Impact toughness(J) Corrosion Embodiment 1 600 251 50 Lower Embodiment 2 600 250 50 Lower Embodiment 3 598 252 50 Lower Embodiment 4 600 250 50 Lower Embodiment 5 605 255 50 Lower Comparative Example 1 590 245 48 Higher Comparative Example 2 595 248 49 Higher Comparative Example 3 570 240 45 Higher Comparative Example 4 570 240 46 Higher

[0145] Among them, low corrosion conditions refer to corrosion rates lower than 0.012 mm / month, and high corrosion conditions refer to corrosion rates greater than 0.0417 mm / month.

[0146] Through the above Table 1, it can be determined directly and uniquely that in Examples 1 to 4, the tensile properties of the steels of Examples 1-4 are close to or reach 600MPa, which indicates that these steels have excellent resistance to deformation during the stretching process. The hardness values ​​of the embodiments are all between 250-252HB, showing that these steels have a uniform hardness distribution. The impact toughness of the embodiments is all 50J, which indicates that these steels can absorb a large amount of energy when impacted and are not easy to break. The corrosion conditions of the embodiments are all "low". This shows that these steels have good corrosion resistance. The steels of these four embodiments show stable tensile properties, uniform hardness distribution, excellent impact toughness and good corrosion resistance.

[0147] The tensile property of Example 5 is 605MPa, which is improved compared to 600MPa of Example 4. This means that Example 5 can withstand a larger load without plastic deformation during the stretching process, and the hardness value of Example 5 is 255HB, which is improved compared to 250HB of Example 4. The increase in hardness indicates that Example 5 has better performance in resisting local pressure or scratches, and the impact toughness of Example 5 remains at 50J, which is the same as Example 4. This shows that under impact loads, the steels of the two embodiments have similar energy absorption capabilities, that is, their impact resistance is equivalent, and the corrosion condition of Example 5 is "lower", which is the same as Example 4. This means that under the same corrosive environment, the steels of the two embodiments have similar corrosion resistance.

[0148] Compared with Example 4, Example 5 has improved tensile properties and hardness, while impact toughness and corrosion conditions remain unchanged. The surface treatment of carbon nanofibers improves tensile properties and hardness, making Example 5 better in bearing loads and resisting local pressure, thereby extending its service life and increasing its application range.

[0149] In Example 4 and Comparative Example 1, where other conditions are the same, niobium is removed from Comparative Example 1. The tensile properties of Comparative Example 1 are 590 MPa, which is lower than the 600 MPa or close to 600 MPa in Examples 1-5. This shows that after removing the niobium element, the tensile properties of the steel material decrease, that is, its ability to resist deformation is weakened. The hardness value of Comparative Example 1 is 245 HB, which is also lower than the range of 250-255 HB in Examples 1-5. The reduction in hardness means that the performance of the steel material in resisting local pressure or scratching is weakened, and it is more susceptible to wear. The impact toughness of Comparative Example 1 is 48 J, slightly lower than 50 J in Examples 1-5. Although the difference is not large, it also shows that after removing the niobium element, the ability of the steel material to absorb impact energy is weakened. The corrosion condition of Comparative Example 1 is "higher", which is in contrast to the "lower" in Examples 1-5. After removing the niobium element, the corrosion resistance of the steel material is significantly reduced, and it is more susceptible to erosion by corrosive media.

[0150] Refer to the instruction manual Figure 1-2 After removing the niobium element in Comparative Example 1, the tensile properties, hardness, impact toughness and corrosion of the steel all decreased, indicating that niobium plays an important role in steel.

[0151] Comparative Example 2 removes the application of nanofibers in high-strength steel. The tensile properties of Comparative Example 2 are 595MPa, which is lower than 600MPa in Examples 1-5, indicating that the tensile properties of the steel material decrease after the removal of carbon nanofibers. The hardness value of Comparative Example 2 is 248HB, which is also lower than the range of 250-255HB in Examples 1-5. The reduction in hardness means that the performance of the steel material in resisting local pressure or scratching is weakened. The impact toughness of Comparative Example 2 is 49J, slightly lower than 50J in Examples 1-5, indicating that the ability of the steel material to absorb impact energy is weakened after the removal of carbon nanofibers. The corrosion condition of Comparative Example 2 is "high", indicating that the corrosion resistance of the steel material is also significantly reduced after the removal of carbon nanofibers. Carbon nanofibers help to form a protective layer on the surface of steel or improve the corrosion resistance of steel, so their removal will lead to a decrease in corrosion.

[0152] After removing the carbon nanofibers in Comparative Example 2, the tensile properties, hardness, impact toughness and corrosion of the steel all decreased.

[0153] Comparative Example 3 removes the application of manganese in high-strength steel. The tensile property of Comparative Example 3 is 570MPa, which is significantly lower than the 600MPa or close to 600MPa values ​​in Examples 1-5. This shows that after removing the manganese element, the tensile property of the steel material is significantly reduced. The hardness value of Comparative Example 3 is 240HB, which is also lower than the 250-255HB range in Examples 1-5. The significant reduction in hardness means that the performance of the steel material in resisting local pressure or scratching is significantly weakened, and it is more susceptible to wear. The impact toughness of Comparative Example 3 is 45J, which is significantly lower than the 50J in Examples 1-5. After removing the manganese element, the ability of the steel material to absorb impact energy is significantly weakened, that is, its impact resistance is significantly reduced.

[0154] After removing the manganese element in Comparative Example 3, the tensile properties, hardness, impact toughness and corrosion of the steel were significantly reduced.

[0155] Comparative Example 4 removes the application of niobium and carbon nanofibers in high-strength steel. The tensile properties of Comparative Example 4 are 570MPa, which is significantly lower than 600MPa in Examples 1-5. This shows that after removing niobium and carbon nanofibers at the same time, the tensile properties of the steel material decrease significantly, and the ability to resist deformation is significantly weakened. The hardness value of Comparative Example 4 is 240HB, which is also lower than the range of 250-255HB in Examples 1-5. The significant reduction in hardness means that the performance of the steel material in resisting local pressure or scratching is significantly weakened, and it is more susceptible to wear. The impact toughness of Comparative Example 4 is 46J, which is still significantly lower than 50J in Examples 1-5. This shows that after removing niobium and carbon nanofibers at the same time, the ability of the steel material to absorb impact energy is weakened, and the corrosion condition of Comparative Example 4 is "higher", which is in sharp contrast to the "lower" in Examples 1-5. This shows that after removing niobium and carbon nanofibers at the same time, the corrosion resistance of the steel material is significantly reduced, and it is more susceptible to erosion by corrosive media.

[0156] In Comparative Example 4, after removing niobium and carbon nanofibers at the same time, the tensile properties, hardness, impact toughness and corrosion of the steel were significantly reduced.

[0157] In summary, the present invention fully utilizes the fine grain strengthening and dispersion strengthening effects of niobium through a carefully designed multi-element alloying strategy, significantly improves the strength and toughness of the steel, and further optimizes the comprehensive properties of the steel by adding other elements.

[0158] The addition of manganese effectively improves the hardenability of steel and promotes the transformation of austenite to high-strength structure, thereby enhancing the strength and ductility of steel. Silicon improves the hardness and resistance to elasticity loss of steel through the solid solution strengthening mechanism. At the same time, it synergizes with elements such as niobium to further refine the grains and improve the microstructure of steel. The precise control of the addition of trace elements of gallium, thallium, tellurium, and antimony, using the cavitation effect and mechanical vibration of ultrasound, ensures the uniform dispersion of these elements in the molten steel, which has a positive effect on the specific properties of steel such as corrosion resistance and fatigue resistance. In addition, the introduction of carbon nanofibers, with its excellent mechanical properties and nano effect, further enhances the strength and toughness of steel and optimizes the microstructure of steel.

[0159] In summary, the niobium-containing microalloyed high-strength steel of the present invention not only achieves a significant improvement in strength through the synergistic effect of multiple alloying elements, but also comprehensively improves the toughness, corrosion resistance, welding performance, forming performance, wear resistance and fatigue resistance of the steel, providing industrial production with advanced materials with excellent performance and significant economic benefits.

[0160] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A niobium-containing microalloyed high-strength steel, characterized in that: The invention comprises the following components in parts by weight: 90-95 parts of iron, 0.05-0.2 parts of niobium, 0.01-0.05 parts of gallium, 0.001-0.01 parts of thallium, 0.01-0.05 parts of tellurium, 0.01-0.1 parts of antimony, 0.3-0.8 parts of carbon, 1-3 parts of manganese, 0.5-2 parts of silicon and 0.05-0.2 parts of carbon nanofiber.

2. The niobium-containing microalloyed high-strength steel according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 93 parts of iron, 0.1 parts of niobium, 0.03 parts of gallium, 0.005 parts of thallium, 0.03 parts of tellurium, 0.05 parts of antimony, 0.5 parts of carbon, 2 parts of manganese, 1 part of silicon and 0.1 parts of carbon nanofiber.

3. The niobium-containing microalloyed high-strength steel according to claim 1, characterized in that: The average grain size of the iron is between 10 and 15 μm, the ellipticity of the niobium is between 1.2 and 1.5, the average particle size of the carbide particles formed by the carbon and niobium is between 50 and 70 nm, and the fiber diameter of the carbon nanofiber is between 10 and 50 nm.

4. The niobium-containing microalloyed high-strength steel according to claim 1, characterized in that: The manganese exists in the steel in the form of precipitates, and the average particle size of the precipitates is 50-100 nm. The silicon exists in the steel in the form of solid solution, and part of the silicon forms compounds in the steel, and the particle size of the compounds is 50-80 nm.

5. The niobium-containing microalloyed high-strength steel according to claim 1, characterized in that: In the microstructure of the steel, niobium carbide particles are uniformly distributed at grain boundaries and within grains, and at least 50% of the niobium carbide particles are adjacent to carbon nanofibers to form a strengthening phase network; The carbon nanofibers form a three-dimensional interwoven network in the material. The carbon nanofibers serve as a guiding structure to guide the crystals to grow in the horizontal direction. The niobium element exists in the form of precipitates. These precipitates interact with the carbon nanofibers. The precipitates gather around the carbon nanofibers to form a precipitate shell. In the area where the precipitate shell interacts with the carbon nanofibers, a twin structure is formed. Assuming the possibility of the formation of the twin structure is P, then: Where A is a constant related to material properties; ΔE is the energy required for twin formation; U eff is a measure of the effective interaction energy between the precipitate and the carbon nanofiber; k is the Boltzmann constant; T is the absolute temperature; R eff is the effective crystal growth rate; C eff is the effective precipitate concentration at the key position for twin formation.

6. A method for producing a niobium-containing microalloyed high-strength steel according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Add iron into the induction furnace for preliminary smelting, and adjust the smelting temperature and atmosphere to remove impurities and adjust the initial composition of the molten iron; S2: When the temperature of the molten iron decreases, niobium is slowly added and mechanical stirring is performed to ensure that niobium is evenly distributed in the molten iron; S3: After the niobium element is added and evenly distributed, add manganese with a higher melting point first, and then add silicon after it is fully dissolved; S4: Finally, trace elements of gallium, thallium, tellurium and antimony are added, and the ultrasonic generator is turned on to utilize the cavitation effect and mechanical vibration of the ultrasonic wave to promote the uniform dispersion of the trace elements in the molten iron; S5: gradually adding carbon and, at the same time, adjusting the carbon content in the molten steel by blowing oxygen; S6: before the end of smelting, when the temperature of the molten steel drops to a certain range, slowly add the carbon nanofibers, and evenly disperse the carbon nanofibers in the molten steel through an ultrasonic vibration disperser, and start a high-speed rotating stirrer while adding the carbon nanofibers to further promote the even dispersion of the carbon nanofibers in the molten steel; S7: After adding all the elements, the temperature of the molten steel is kept stable to ensure that all the elements and the carbon nanofibers fully react and combine; S8: Casting the treated molten steel into a mold, cooling and solidifying to obtain a casting, and obtaining a niobium-containing microalloyed high-strength steel. During the casting process, the casting speed and cooling rate need to be controlled to avoid defects in the casting.

7. The method for producing niobium-containing microalloyed high-strength steel according to claim 6, characterized in that: In S3, after the niobium element is added and evenly distributed, the temperature of the molten iron is maintained at 1400-1450°C, and manganese with a higher melting point is added first. After manganese is fully dissolved and the temperature of the molten iron drops to 1350-1400°C, silicon is added. The addition rate of manganese and silicon is controlled at 4-6 kg / min, and the stirring intensity is 200-300 rpm to ensure the uniform distribution of these elements in the molten iron.

8. The method for producing niobium-containing microalloyed high-strength steel according to claim 6, characterized in that: In the S6, before the end of smelting, when the temperature of the molten steel drops to 1200-1300°C, carbon nanofibers are slowly added, and the length of the carbon nanofibers is controlled between 10 and 50 μm. The carbon nanofibers are evenly dispersed in the molten steel by an ultrasonic vibration disperser, and the power of the ultrasonic vibration disperser is set to 2-3 kW. While adding the carbon nanofibers, a high-speed rotating agitator is turned on for stirring, and the speed is set to 200-400 rpm, so as to further promote the uniform dispersion of the carbon nanofibers in the molten steel.

9. The method for producing niobium-containing microalloyed high-strength steel according to claim 6, characterized in that: In S6, the carbon nanofibers are subjected to surface modification treatment by exposing them to an oxidizing gas to introduce oxygen-containing functional groups onto the surface of the carbon nanofibers. At the same time, a thin organic coating is coated on the surface of the carbon nanofibers to change their surface properties.

Citation Information

Patent Citations

  • A thin cast strip product with microalloy additions, and method for making the same

    CN101765469A

  • A thin cast strip product with microalloy additions, and method for making the same

    CN101765470A

  • Hot-rolled steel sheet and process for manufacturing same

    CN104011234A

  • Niobium microalloying high-carbon chromium bearing steel and hot rolling production method thereof

    CN104032221A

  • Carbide and intermetallic compound composite reinforced ultra-high-strength steel and preparation method of bar of carbide and intermetallic compound composite reinforced ultra-high-strength steel

    CN115478212A